Brief overview of the integrated curriculum in Nepal: Key features, impacts and challenges - Kunwar, Rajendra; C., Laxmi G.; Acharya, Narahari; Adhikari, Sapana (Journal of Research in Instructional, 2024)
This article provides a brief overview of the integrated curriculum of Nepal. It uses the desk review method. It delves into the context of curriculum development and its rationale in the Nepalese context, emphasizing the need for a shift towards an integrated approach. The article explores the integration of the current basic level (grades 1-3) curriculum and discusses the continuum of curriculum integration. It highlights the evolving concept of an integrated curriculum and sheds light on its key features. Additionally, the article discusses the challenges of implementing an integrated curriculum in the Nepalese context. It explores the impact of integrated curriculum on the Nepalese education system, and students' learning, such as the development of soft skills, critical thinking, and interdisciplinary skills. The article also provides recommendations for promoting integrated curriculum practices and emphasizes the importance of teacher professional development and stakeholders' participation for effective implementation.